Evaluation Model for developing effective indicators for health surveillance actions in Brazil - Eronildo Felisberto; Rodrigo Lino de Brito; Danila Augusta Accioly Varella Barca; Mary Anne Fontenele Martins; Adriana Karla N. B. Marinho de Oliveira; Nidia Cristina de Souza; Ana Paula Neves Marques de Pinho; Jarbas Barbosa da Silva Júnior; Isabella Samico
Abstract Objective: to present an evaluation model for developing effective indicators for the Vigilância Sanitária (VISA) (Sanitary and Health Surveillance) actions in Brazil. Methods: an exploratory, evaluative study from primary sources data - electronic form by key informants and reports on national, international and secondary benchmarking visits - documental analysis. Results: the diversity of VISA management practices made it possible to define the evaluation object: Health Surveillance Actions - as an organized action system. The components: management; regulation; sanitary and health control; sanitary and health risk monitoring and information, communication and health education were derived from the aims of the intervention and composes a central structure of the Theoretical Model and the Logical Model Actions of VISA in the Sistema Nacional de Vigilância Sanitária (SNVS) (National Sanitary and Health Surveillance System) . Conclusions: The Vigilância Sanitária (VISA) (Sanitary and Health Surveillance) accumulates experience with the process indicators for monitoring actions, being incipient are capable of evaluating its impact. The theoretical resources in the evaluation area support the information management in the VISA field and besides contributing for studies on social determinants and the incorporation of analyses in historic series.